Inventory of rice weed species in the rice paddies Village Kutelintang District Blangkejeren Gayo Lues District - Siti sahrah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
The research about inventory of rice weed species on paddy field in Kutelintang Village, Blangkejeren district has been done from July to October 2019. The study was aimed to determine species and types of weeds in paddy fields of Kutelintang Village, Blangkejeren. Data was collected by survey exploration. The location was divided into four stations based on points of the compass. Data was analysed descriptivelly. The result shows that there were 50 spesies of weeds belong to 26 families. The types of weed were Poaceae, Cyperaceae and broadleaf weeds. Types of broadleaf weeds had the most members/species which were 39 species belonging to 24 families followed by Poaceae (6 species) and the least was Cyperaceae (5 species).  The spesies of broadleaf weed belonged to 24 familia which were Apiaceae, Asteraceae, Verbenaceae,        Ranunculaceae, Solanaceae, Fabaceae, Polygonaceae, Convovulaceae, Araliaceae, Passifloraceae, Plantaginaceae, Amaranthaceae, Euphorbiaceae, Alismataceae, Onagraceae, Portulacaceae, Pontederiaceae, Marsileaceae, Boraginaceae, Malvaceae, Commelinaceae, Araceae, Rubiaceae, Dryopteridaceae. Therefore, it can be concluded that the weeds in Kutelintang paddy field vary in spesies, family and type. Moreover,  broadleaf weed is the most familiar type found in the study area.